2022
DOI: 10.3390/life13010091
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Inflammatory Markers and Vitamin D Relationship in Pediatric Patients

Abstract: Background: Biomarkers play an important role in COVID-19, and more research in this regard is needed, especially in the case of children. This study aimed to look for a link between the C reactive protein (CRP), lactate dehydrogenase (LDH), creatine kinase (CK), vitamin D and COVID-19 in pediatric patients. Methods: This is a retrospective cohort study, performed on children diagnosed positively with COVID-19 at a children’s hospital in western Romania. Available CRP, LDH, CK vitamin D and clinical severity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 48 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…In a previous study, it was established that CRP was higher in older children and adolescents, whose immune system is more developed, and, hence, more akin to that of adults’ and elders’ [ 33 ]. Following a retrospective analysis of a group of 3424 children in Indonesia, it was concluded that CRP levels may be a good indicator for the treatment and early identification of the disease in children [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was established that CRP was higher in older children and adolescents, whose immune system is more developed, and, hence, more akin to that of adults’ and elders’ [ 33 ]. Following a retrospective analysis of a group of 3424 children in Indonesia, it was concluded that CRP levels may be a good indicator for the treatment and early identification of the disease in children [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major laboratory markers that were studied by Romanian authors are displayed in Table 1. Yes, even more so in Roma [53,54,[58][59][60][61][62]70] Diabetes [48,94] Antiphospholipid syndrome [47] Hypertension [27] Cardiac dysfunction [46,73,93] Overweight/metabolic syndrome [27,54,93] Lung involvement [50,57] PIMS [83] Chronic Spontaneous Urticaria Exacerbation [42] Pneumothorax/ pneumomediastinum [31,72] Liver failure [44] Multiple organ dysfunction [ [57,58,102,103] No [55] More comorbidities [29,101] Lung involvement [57] In addition, this article aimed to identify gaps in this research and provide encouragement for Romanian research to focus on novel and detailed aspects of the pandemic. For instance, as Romania grapples with the aftermath of the COVID-19 pandemic, understanding the long-term effects of the disease is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzed the relationship/role of vitamin D levels/supplementation in incidence/severity of respiratory tract infections, including COVID-19 [7][8][9]. Studies regarding the relationship between vitamin D and COVID-19 clinical and laboratory profile or disease outcomes, mainly focused on adult patients and often showed conflicting results [10][11][12][13][14][15][16][17][18][19][20][21][22]. A series of studies identified a negative correlation between vitamin D and NLR and CRP [12,13], while other studies did not identify any correlation between them [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding the relationship between vitamin D and COVID-19 clinical and laboratory profile or disease outcomes, mainly focused on adult patients and often showed conflicting results [10][11][12][13][14][15][16][17][18][19][20][21][22]. A series of studies identified a negative correlation between vitamin D and NLR and CRP [12,13], while other studies did not identify any correlation between them [14][15][16][17]. The study of Yarali et al [18] reported that in SARS-CoV-2 infection in children, the leukocytes count was normal, while the study of Yamada et al [19] reported the association between leukocytosis and a poor outcome.…”
Section: Introductionmentioning
confidence: 99%